Hepatoprotective Effects of Silybum Marianum Extraction Against Acetamiprid-Induced Stress Oxidative in Male Rats: Potential Anticancer Application - Noory Fajer, Ali; Nasser Hussein, Meaad (Asian Pacific Journal of Cancer Biology, 2024)
Objective: Silybum marianum, commonly known as milk thistle, has been extensively studied for its hepatoprotective effects. While most documented data focus on its benefits for liver disorders, recent research has highlighted its protective effects on other organs such as the kidneys. Studies have shown that Silybum marianum exhibits antioxidant, lipid-lowering, antihypertensive, antidiabetic, antiatherosclerotic, anti-obesity, and hepatoprotective properties. Materials and Methods: In the present study we investigated the protective effect of aqueous extraction of Silybum marianum against acetamiprid-induced (N’-cyano-N-methyl-acetamidine phosphorothioate) stress oxidative on liver and kidney function by evaluating the serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine, and urea in male rats. Furthermore, an anatomical study was conducted on the liver and kidney to enhance the research. Results: The results showed the effective impacts of aqueous extraction of Silybum marianum on AST, ALT, creatinine, and urea serum levels. There was also a protective effect in the group of rats fed with both acetamiprid and extraction of Silybum marianum compared to the group fed with only acetamiprid. Conclusion: Our results revealed that Marianum extract can reduce hepatotoxic and nephrotoxic effects caused by acetamiprid and has anti-hepatocyte cancer potential.